Outcomes of patients with low-risk differentiated thyroid cancer with an excellent response to initial therapy - Carlos Garcia-Regal; Jhonatan Quiñones-Silva; Noemi Brox-Torrecilla; Alberto Martinez-Lorca; Ignacio Ruz-Caracuel; Héctor Pian Arias; Sonsoles Aso Manso; Ana Maria Garcia Cano; Marta Rosillo; Patricia Luengo; Belén Porrero Guerrero; Maria Isabel García Gómez Muriel; et al. (European Thyroid Journal, 2026)
Abstract Objective Patients with differentiated thyroid carcinoma (DTC) classified as low risk of recurrence and an excellent response to initial treatment should have a particularly low risk of recurrence. Our objective was to assess the recurrence rate in these patients to support follow-up de-escalation. Methods A multicentre retrospective study was conducted in six Spanish hospitals, including consecutive patients diagnosed with low-risk DTC between 2015 and 2018 with an excellent response to initial therapy. Results A total of 379 patients were included, with a median follow-up of 6.7 years. Response to therapy at last follow up, according to the 2015 ATA/Momesso criteria was excellent in 349 patients (92.1%), indeterminate in 29 (7.6%), and biochemically incomplete in 1 (0.3%). The overall incidence of indeterminate response was 11.8 events per 1,000 person-years, peaking at year three of follow-up and dropping to near zero after year seven. PTC and RAI treatment were associated with a lower probability of developing an indeterminate response (p=0.02 and p=0.03, respectively). When applying the 2025 ATA criteria, the excellent response rate increased to 95.8% and neither papillary histology nor RAI treatment were significantly associated (p=0.07 and p=0.61, respectively). During follow up, indeterminate/suspicious findings on ultrasound were observed in 39 patients (10.3%). FNA was performed in 20 of these, none of which found recurrence. Conclusions Recurrences in patients with low risk of recurrence and an excellent response to initial therapy are extremely infrequent. These data support follow-up de-escalation in this population.